Prognostic value of combining preoperative immune-inflammatory-nutritional index and tumor biomarkers in gastric cancer patients undergoing radical resection - Du, Yongtao; Li, Yunlong; Tan, Zhaobang; Song, Jiawei; Jiang, Yu; Liu, Shuai; Guo, Yajie; Qiao, Yihuan; Zhu, Jun; Li, Shisen; Li, Jipeng (Frontiers in Nutrition, 2025)
BackgroundGastric cancer (GC) patients frequently face the debilitating comorbidity of malignant cachexia, a condition that consistently forecasts a dismal prognosis. Early diagnosis of cachexia and timely prediction of survival outcomes are essential for them. Here, we aimed to construct an immune-inflammatory-nutritional-tumor-marker (IINTM) prognostic score for GC, and further scrutinize its clinical relevance in early forecasting the cachexia.MethodA total of 1,101 GC patients underwent curative surgical were incorporated in our study, and they were evaluated by the Computed Tomography (CT) of skeletal muscle mass at third lumbar spine plane levels (SMI-L3). Using restricted cubic spline (RCS) analysis, we examined associations between prognosis and nutritional indices, including the Prognostic Nutritional Index (PNI) and Systemic Immune-Inflammation Index (SII). The IINTM score was constructed by the multivariate Cox analysis and evaluated by the Receiver Operating Characteristic (ROC) and area under the ROC (AUC).ResultsWe identified striking discrepancies in immunonutrition profiles and prognoses between cachexia and non-cachexia GC patients. Patients with cachexia had worse prognosis and lower SMI-L3 scores than those without cachexia. The IINTM score, incorporating PNI, SII, body mass index (BMI), NRS2002, serum albumin, platelet, D-dimer, CEA, and CA199, exhibited a high concordance index (C-index) of 0.784, underscoring its robust predictive efficacy. Most crucially, IINTM score demonstrated substantial diagnostic value for cachexia, with an AUC of 0.858, denoting its high degree of accuracy.ConclusionThe IINTM score could be a reliable tool and precisely predict the cachexia and prognosis for GC patients. Our findings provide novel insights into the role of immune-inflammatory-nutrition, tumor marker and cachexia in GC patients.